Tolerability and efficacy of adjunctive brivaracetam in adults with focal seizures by concomitant antiseizure medication use: Pooled results from three phase 3 trials. Issue 8 (10th June 2022) - Ryvlin, Philippe; Dimova, Svetlana; Elmoufti, Sami; Floricel, Florin; Laloyaux, Cédric; Nondonfaz, Xavier; Biton, Victor
Abstract: Objective: This study was undertaken to evaluate safety/tolerability and efficacy of adjunctive brivaracetam (BRV) in patients on one or two concomitant antiseizure medications (ASMs) and in patients on one specific concomitant ASM. Methods: Post hoc analysis was made of double‐blind trials (N01252/NCT00490035, N01253/NCT00464269, and N01358/NCT01261325) in adults with focal seizures randomized to BRV (50–200 mg/day; approved therapeutic dose range for adults) or placebo with concomitant ASM regimen unchanged throughout a 12‐week evaluation period. Outcomes were analyzed in patients on one or two concomitant ASMs, and those on concomitant carbamazepine (CBZ), lamotrigine (LTG), oxcarbazepine (OXC), or valproate (VPA) only. Results: Patients randomized to BRV with one or two concomitant ASMs, respectively ( n  = 181/557), reported similar incidences of treatment‐emergent adverse events (TEAEs; 68.0%/66.4%), drug‐related TEAEs (41.4%/41.5%), and TEAEs leading to discontinuation (6.6%/5.4%). Respective values for patients randomized to placebo with one or two concomitant ASMs ( n  = 95/331) were 60.0%/60.7% (TEAEs), 32.6%/30.2% (drug‐related TEAEs), and 2.1%/4.5% (TEAEs leading to discontinuation). The incidences of TEAEs, drug‐related TEAEs, and TEAEs leading to discontinuation by specific concomitant ASM (CBZ, LTG, OXC, VPA) were similar to the overall incidences in patients taking one concomitant ASM. In patients on one or two concomitant ASMs, respectively, 50% responder rates were numerically higher on BRV (42.3%/36.8% [ n  = 175/511]) versus placebo (18.3%/19.5% [ n  = 93/298]). Patients with one or two ASMs on BRV ( n  = 175/509) versus placebo ( n  = 92/298) also had numerically higher 100% responder rates (BRV, 9.1%/4.5%; placebo, 1.1%/.3%) and seizure freedom (6.9%/3.7%; 1.1%/0). For patients taking concomitant CBZ, LTG, OXC, or VPA, efficacy was numerically higher with BRV ( n  = 54/30/27/27) versus placebo ( n  = 34/13/10/14–15; 50% responder rates: BRV, 31.5%/30.0%/40.7%/70.4%; placebo, 17.6%/7.7%/20.0%/33.3%; 100% responder rates: BRV, 5.6%/10.0%/11.1%/11.1%; placebo, 0 for all; seizure freedom: BRV, 3.7%/6.7%/7.4%/11.1%; placebo, 0 for all). Significance: Therapeutic doses of BRV were efficacious and well tolerated regardless of the number of concomitant ASMs (one or two) or specific concomitant ASM (CBZ, LTG, OXC, VPA).